Plan de marketing digital para el posicionamiento comercial de ARTECUA en la provincia de Imbabura. - García, Mauricio D. (2022)
This work deals with the lack of application of new technologies specifically of electronic commerce and digital marketing in the wood furniture sector of the city of San Antonio de Ibarra. The text highlights the importance that today represents for companies to sell by digital means, which has become significant, since as a result of the pandemic caused by COVID-19, the distribution channel that will boost commerce was based on the use of digital platforms to reach the customer. For this reason, organizations that have not yet entered this new marketing trend, as a communication and distribution support strategy, may be relegated to the medium and long term, while those that implement it may become the next leaders of the market. market. Artecua is a family business with extensive experience in the sector of production and sale of wooden furniture that has seen its sales decreased by up to 70% due to the COVID19 pandemic, which is why the generation of a digital marketing plan stands as a necessary and invaluable opportunity to conquer new markets. The document includes an analysis of the sector, the application of an academically recognized methodology and the presentation of results. The research yields data of great value such as the interest of people in digital media and not in traditional media, the low interest of the artisan and wooden furniture sector for plans of these characteristics. Finally, it is evident that with a budget within the reach of the Artecua company, it is possible to execute a digital marketing plan that achieves important objectives of brand positioning in Ecuador and the recovery of sales through BTL media, specifically lowcost digital platforms. cost in the medium and long term.